2023
DOI: 10.1111/spc3.12817
|View full text |Cite
|
Sign up to set email alerts
|

Social influences on mask‐wearing intentions during the COVID‐19 pandemic

Abstract: Face mask‐wearing is important for reducing COVID‐19 spread. Masking is a publicly visible behavior and thus, social factors such as descriptive and personal norms, risk images, and impression management concerns are salient and likely influential. Study 1 (N = 381) surveyed participants during the early stages of the pandemic, assessing correlational relationships between social factors and masking intentions. Study 2 (N = 778) replicated Study 1 at a later stage in the pandemic and experimentally manipulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These studies assert that biospheric values encourage a person to act in an environmentally friendly way, and personality characteristics of considering future consequences for current action make a drive within him or her to choose green products (Shin, Fan, Tang, 2023). Simultaneously, the scholars also endorse the vitality of injunctive social norms (Doran & Larsen, 2016; and descriptive social norms (Goldstein, Cialdini, & Griskevicius, 2008;Lipsey & Losee, 2023) to create buying intentions. Descriptive norms describe the info about prevailing appropriate conduct and behavior in the society dependent on the apprehension regarding the actions of people usually be done (Ryoo & Kim, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies assert that biospheric values encourage a person to act in an environmentally friendly way, and personality characteristics of considering future consequences for current action make a drive within him or her to choose green products (Shin, Fan, Tang, 2023). Simultaneously, the scholars also endorse the vitality of injunctive social norms (Doran & Larsen, 2016; and descriptive social norms (Goldstein, Cialdini, & Griskevicius, 2008;Lipsey & Losee, 2023) to create buying intentions. Descriptive norms describe the info about prevailing appropriate conduct and behavior in the society dependent on the apprehension regarding the actions of people usually be done (Ryoo & Kim, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Injunctive norms, on the other hand, reflect beliefs about how one ought to act based on expectations of what other people would morally approve or disapprove of (Hansen et al, 2018). Doran and Larsen (2016) , as well as Lipsey and Losee (2023), suggested that descriptive social norms and injunctive social norms both activate and promote buying intentions toward green products. The past literature shows a direct link of personal norms and social and psychological factors with buying intentions towards green products.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation